Persepsi Kebermanfaatan, Appearance, dan Individualism terhadap Penggunaan E-Filing dengan Kepuasan Pengguna sebagai Variabel Intervening - Tahar, Afrizal; Jilan Sabiqoh, Alya (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p20, 2020)
This study aimed to analyze effect of perceived usefulness, appearance, and individualism to use e-Filing with user satisfaction as an intervening variable. This study used primary data collected from UMKM Taxpayer in Rejang Lebong Regency. This study revealed seven hypotheses tested using SEM-PLS analysis tools through the SmartPLS version 3.3.2 application. The results showed that perceiced of usefulness had a posittive effect to use e-Filing, while appearance and individualism did not significantly influence taxpayer to use e-Filing. In addition, user satisfaction mediate the relationship among appearance to use e-Filing. Meanwhile,  user satisfaction did not mediate the relationship among perceived usefulness and individualism to use e-Filing. Keywords: E-Filing; Perceived Usefulness; Appearance; Individualism; User Satisfaction.